2013
DOI: 10.1111/tid.12067
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive intravenous immunoglobulin allows safe and timely administration of antineoplastic therapies in patients with multiple myeloma and parvovirus B19 disease

Abstract: Parvovirus B19 can cause severe disease in myeloma patients including ASCT recipients. Thrombocytopenia - not anemia - was the leading presentation and may be associated with autoimmune conditions. Patients with unexplained cytopenias, particularly when prolonged, should undergo testing for circulating parvovirus. A reduction in viral load was associated with response to IVIG, although additional therapy was needed for recurrent disease. Most importantly, preemptive IVIG allowed for safe and timely administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Good hand washing is critical and the most important single method of infection control (Katragadda et al, 2013). Close contact with individuals who have respiratory symptoms or fever should be avoided when possible and frequent hand washing is advised (Leifeldt et al, 2002).…”
Section: Prevention and Vaccine Developmentmentioning
confidence: 99%
“…Good hand washing is critical and the most important single method of infection control (Katragadda et al, 2013). Close contact with individuals who have respiratory symptoms or fever should be avoided when possible and frequent hand washing is advised (Leifeldt et al, 2002).…”
Section: Prevention and Vaccine Developmentmentioning
confidence: 99%
“…In contrast, it has been reported that persistent PVB infection could be established in immunosuppressed conditions where the ability to constitute effective antiviral immunity is severely impaired. These conditions include human immunodeficiency virus infection, hematological diseases, HSCT, and solid organ transplantation . In addition to our case, only one case of MM has been reported in which persistent PVB infection was documented and caused RCA .…”
Section: Discussionmentioning
confidence: 58%
“…Regarding the doses of immunoglobulin, our patient responded well with a relatively lower dose (in total 300 mg/kg) compared with the previously reported doses ranging between 1500 and 4000 mg/kg . Because of the high cost of high‐dose IVIg administration, the efficacy of lower doses should be investigated by accumulating the outcomes of patients treated with lower doses.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations